Tadabbur Al-Quran to Decrease Anxiety Among Students Facing National Examination - Sustring, Hasna Fadilla; Wijaya, Hariz Enggar (Universitas Muhammadiyah Surakarta, 2019)
This literature review aims to find out how much influence Qur’an has to reduce the anxiety experienced by students facing the National Examination. The national examination is a routine agenda carried out to assess and see students’ abilities in mastering learning material during their education process. Towards the national examination, many students who feel anxious and worried about their ability to do the national examination, this situation is anxious. Some researchers applied the method with tadabbur Qur’an, the results obtained indicate this method was effective in reducing student anxiety facing the national examination. Students can control anxiety, bring a calm heart, and this condition will increase the concentration of students while dealing with a problem. Become more positive, healthier physically and psychologically, feel confident, and reduce unnecessary worries or fears about national examinations.